Low dose paracetamol for management of patent ductus arteriosus in very preterm infants: a randomised non-inferiority trial. Issue 2 (8th August 2022) - Balasubramanian, Haribalakrishna; Jain, Vaibhav; Bhalgat, Parag; Parikh, Shalin; Kabra, Nandkishore; Mohan, Diwakar; Sheth, Kshitij
Abstract : Objective: To compare the efficacy of low dose-short course intravenous paracetamol with a conventional dose regimen for early targeted closure of patent ductus arteriosus (PDA). Design: Single-centre, double-blinded, active controlled, randomised non-inferiority trial. Setting: Level III neonatal intensive care unit in Western India. Patients: Preterm infants <30 weeks of gestation requiring mechanical ventilation, or continuous positive airway pressure with FiO2 ≥0.35 and diagnosed with a haemodynamically significant PDA (hsPDA) at 18–24 hours of postnatal age. Interventions: Low dose (10 mg/kg/dose 6 hourly for 72 hours) versus conventional dose (15 mg/kg/dose 6 hourly for 120 hours) intravenous paracetamol treatment. Main outcome measures: Comparison of the rates of ductal closure at completion of sixth postnatal day, using a prespecified non-inferiority margin of 20%. Results: A total of 102 infants were enrolled. The median gestational age and birth weight of the included infants were 26.4 weeks and 830 g. At completion of the sixth postnatal day, closure of PDA was achieved in 92% of infants in the low dose group as compared with 94% of those in the standard dose group (risk difference: −1.6%, 95% CI: −11.6% to 8.5%, p=0.38). The rates of rescue therapies, adverse effects and other neonatal morbidities were comparable in both groups. Conclusion: In very preterm infants on significant respiratory support, low dose-short course intravenous paracetamol treatment was non-inferior to a conventional dosing regime of paracetamol for closure of hsPDA in the first week of postnatal age. Larger studies with narrow margins of non-inferiority are required to confirm our findings. Trial registration number: CTRI/2017/10/010012. Abstract : Low dose (10 mg/kg, for 3 days) intravenous paracetamol was non-inferior to a conventional high dose (15 mg/kg, for 5 days) regimen for early targeted PDA treatment in very preterm neonates, without difference in adverse effects.